The use of humour in the off-task spaces of the language classroom. (3rd January 2019) - Victoria, Mabel
Abstract: The focal point of most investigations into classroom discourse tends to be on the institutionally sanctioned and legitimized on-task exchanges between teachers and students with particular attention to the I-R-F (initiation–response–follow up/feedback) structure. Liminal spaces of interaction such as during the small talk just before the 'lesson proper', transitions between activities, and playful moments before or immediately after breaks are often unexplored. Using transcribed naturalistic spoken data collected via participant observation over 12 weeks, examples of teacher-initiated humour are analysed to shed light on how off-task, 'non-teaching' spaces can be used as a pedagogical resource. This study puts the spotlight on how humour can be deployed in these obscure interstices of the L2 classroom to create a space not only to build rapport between students and teachers but also to impart new vocabulary and sociocultural knowledge.